Wave speed mapping visualizes the cavotricuspid isthmus reconnection area: A case report - Hiroshi Mase; Hiroyoshi Mori; Tatsuya Onuki; Hiroto Sugiyama; Ayumi Omura; Taku Asano; Hiroshi Suzuki (Clinical Case Reports)
Key Clinical Message In addition to the reentrant map, the wave speed map can be helpful in accurately identifying the CTI gap during radiofrequency application for atrial flutter(AFL). However, in complex cases involving extensive scarring and multiple low‐velocity local areas, this technique may not be useful. Abstract A 73‐year‐old male patient with a history of pulmonary vein isolation and cavotricuspid isthmus ablation underwent a second catheter ablation owing to recurrent atrial flutter (AFL). The AFL was diagnosed as cavotricuspid isthmus‐dependent AFL caused by the reconnection of the previous cavotricuspid isthmus ablation. Wave speed mapping was performed at the same site, and results comprehensively revealed a low‐velocity local area. The AFL was terminated after the first radiofrequency application, and the block line was easily completed. Therefore, this technique could be an adjunctive tool for cavotricuspid isthmus gap identification and minimal radiofrequency application.